American criminal justice : an introduction / Frederick T. Davis. - Davis, Frederick T., 1945- (Cambridge University Press, 2019)
American criminal justice may be one of the best known - and most influential - systems of criminal justice in the world, but also the least understood: countless films and television series portray American police officers, prosecutors and lawyers, but over 95 percent of criminal matters result in guilty pleas, and trials are becoming vanishingly scarce as people accused of crime choose to strike a deal with increasingly powerful prosecutors. Sentencing 'reform' has led to a burgeoning prison population that is by far the highest among economically advanced countries. Meanwhile, American prosecutors have gained increasing (and largely unchecked) power to apply US criminal laws to worldwide corporations and individuals with little or no connection with the country. American Criminal Justice: An Introduction provides a readable, comprehensive review of the American criminal process behind these and other problems.